Evaluasi Perilaku Struktur Gedung Beton Bertulang dengan Metode Elemen Hingga Proyek Pembangunan Banten Islamic Center - Pratama, Rama; Walujodjati, Eko (Jurnal Konstruksi, 2023)
One type of construction is building construction, an important infrastructure in human life and widely used throughout the world. Building construction can be used for various activities, such as residences, offices, shopping centers, and the like. Therefore, technology that can help make building plans easier and more connected is needed, namely calculating the analysis of the building structure using the finite element method (Finite.Element.Method). The evaluation calculation also refers to SNI`1726,1727, and 2847:2019. The load calculation includes wind, earthquake, dead and live loads. The upper and lower structures are the structural components that are analyzed. The results of the evaluation calculation show that the concrete structure is able to withstand the given loads, seen from the 600 x 600 dimension column where the moment acting on the column is 171 kNm while the moment that the column can withstand is 496.7 kNm with a ratio of 0.346 , so it can be said that the structure is very safe, but in terms of efficiency the material used in the column can be said to be wasteful.